Strategi Penanaman Literasi Budaya dan Kreativitas Bagi Anak Usia Dini Melalui Pembelajaran Tari - Sri Wahyuni (Yayasan Citra Dharma Cindekia, 2024)
Cultivating cultural literacy and creativity through dance learning to love their own culture more for early childhood. For this reason, the purpose of this article is to explain the process of inculcating dance literacy and creativity through dance learning in early childhood. This research method is qualitative, data collection is done by observation, interviews, and documentation. The analysis was carried out during the data collection process by making conclusions from the research focus. The results found that the process of cultivating dance literacy through dance learning, children became more aware of various movements and folk songs, appreciated in the form of performing movements and singing other folk songs, conduct analysis, especially related to technique, unconsciously for children have applied knowledge about culture in their lives. The results of the study are related to creativity, for early childhood to become skilled and fluent in dancing, flexible, expressive, and skills in detailing the sequence of movements, as well as the ability to imagine.